Bioremotion of toxic metals from water by spores of bacillus sg1 - Carvajal, Guy (2007)
The process of selective biosorption of Pb and As by bacterial spores was investigated. The microorganism used was Bacillus spp. SGI isolated from the marine environment. Optimum pH values for the adsorption of these toxic metals were found to be between 4 and 7. The spores showed a high affinity for these metals in aqueous solutions. A very high adsorption of Pb and As was observed at initial concentrations of 4 mg/L and under these conditions the sorption isotherms follow the classic Lanfmuir pattern with a regression value of 0.89 and 0.88 for Pb and As, respectively. In terms of a simple practical applicability, plastic bottles containing a mixture of sand and spores activated with manganese were enabled, resulting in an effective removal of 99% and 98% of Pb and As from the water in a period of 1 hour. This simple application can help resolve the decontamination of underground drinking water used in rural communities.